Management of chronic obstructive pulmonary disease—A position statement of the South African Thoracic Society: 2019 update - Abdool-Gaffar, Mohamed Sabeer; Calligaro, Gregory; Wong, Michelle Lianne; Smith, Clifford; Lalloo, Umesh Gangaram; Koegelenberg, Coenraad Frederik Nicolaas; Dheda, Keertan; Allwood, Brian William; Goolam-Mahomed, Akhter; van Zyl-Smit, Richard Nellis (Journal of Thoracic Disease; Vol 11, No 11 (November 28, 2019): Journal of Thoracic Disease, 2019)
Chronic obstructive pulmonary disease (COPD) is a significant cause of death and disability in both developed and developing countries. It is increasing in frequency and demands increasing utilisation of healthcare resources.